2008
DOI: 10.1242/jcs.024588
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary analysis and molecular dissection of caveola biogenesis

Abstract: Caveolae are an abundant feature of mammalian cells. Integral membrane proteins called caveolins drive the formation of caveolae but the precise mechanisms underlying caveola formation, and the origin of caveolae and caveolins during evolution, are unknown. Systematic evolutionary analysis shows conservation of genes encoding caveolins in metazoans. We provide evidence for extensive and ancient, local and genomic gene duplication, and classify distinct caveolin gene families. Vertebrate caveolin-1 and caveolin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
136
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(144 citation statements)
references
References 69 publications
(97 reference statements)
6
136
1
1
Order By: Relevance
“…The ability of CAV-2 to induce the formation of caveolae has not been tested. Kirkham et al, (2008) have shown that C. elegans CAV-1 does not induce caveolae in mammalian cells and have used phylogenetic analysis to indentify amino acid changes that may underlie this difference (Kirkham et al, 2008). In particular they identified two key regions: one involving residues 56 -59 and another involving residues S104, F12, and A129 in the human caveolin 1 sequence (Supplementary Figure S4), which may determine the ability of caveolins to form caveolae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of CAV-2 to induce the formation of caveolae has not been tested. Kirkham et al, (2008) have shown that C. elegans CAV-1 does not induce caveolae in mammalian cells and have used phylogenetic analysis to indentify amino acid changes that may underlie this difference (Kirkham et al, 2008). In particular they identified two key regions: one involving residues 56 -59 and another involving residues S104, F12, and A129 in the human caveolin 1 sequence (Supplementary Figure S4), which may determine the ability of caveolins to form caveolae.…”
Section: Discussionmentioning
confidence: 99%
“…The behavior of CAV-1 in the germ line and embryos is highly dynamic . Phylogenetic analysis and expression studies of CAV-1 and CAV-1-mammalian caveolin hybrids in mammalian cells suggest that CAV-1 does not induce caveola biogenesis (Kirkham et al, 2008) and so may have a different role to mammalian caveolins. The function of CAV-2 has not previously been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…It is unclear whether the effect results from increased levels of CAV-1 in tissues which normally express the CAV-1 protein or , is due to ectopic expression. It has recently been suggested that C. elegans CAV-1 is unlikely to form caveolae, 23 thus making its role in this and other processes in C. elegans enigmatic.…”
Section: Article Addendummentioning
confidence: 99%
“…Egg laying in C. elegans is under neuronal control thus changes in egg laying may be the result of changes in neuronal function brought about by the presence of ectopic CAV-2 protein. The ability of CAV-2 to form caveolae has not been tested; 23 however, bioinformatic analysis Overexpression of caveolins in C. elegans Figure 1. Overexpression of CAV-1 improves fecundity in heat-shocked worms carrying extrachromosomal arrays.…”
Section: Overexpression Of Caveolin-2 Causes Increased Egg Layingmentioning
confidence: 99%
“…Кавеолины -чрезвычайно «консервативные бел-ки», а их гомологи обнаружены у различных предста-вителей Metazoa [18].…”
unclassified